Purines, Purinergic Receptors, and Cancer - Di Virgilio, Francesco (Cancer research (Chicago, Ill.), 2012)
Purines were long thought to be restricted to the intracellular compartment, where they are used for energy transactions, nucleic acid synthesis, and a multiplicity of biochemical reactions. However, it is now clear that both adenosine and adenosine triphosphate are (i) abundant biochemical components of the tumor microenvironment, (ii) potent modulators of immune cell responses and cytokine release, and (iii) key players in host–tumor interaction. Moreover, both ATP and adenosine directly affect tumor cell growth. Adenosine is a powerful immunosuppressant (mainly acting at A2A receptors) and a modulator of cell growth (mainly acting at A3 receptors). ATP is a proinflammatory (acting at P2Y1, P2Y2, P2Y4, P2Y6, and P2Y12, and at P2X4 and P2X7 receptors), an immunosuppressant (acting at P2Y11), and a growth-promoting agent (acting at P2Y1, P2Y2, and P2X7 receptors). This complex signaling network generates an array of inhibitory and stimulatory responses that affect immune cell function, tumor growth, and metastatic dissemination. Investigation of purinergic signaling has increased our understanding of the tumor microenvironment and opened new and exciting avenues for the development of novel therapeutics. Cancer Res; 72(21); 5441–7. ©2012 AACR.